First DNA barcode reference library for the identification of South American freshwater fish from the lower Paraná River - Díaz, Juan (2016)
Fil: Fil: Díaz, Juan. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Biología Molecular y Celular de Rosario (IBR -CONICET); Argentina.